Dietary Exposure Assessment of Trans-Fatty Acids through Consumption ofIce-Cream in Yerevan, Armenia - Pipoyan, D. A.; Beglaryan, M. R.; Stepanyan, S. A.; Gharibyan, G. K. (ՀԱԱՀ հիմնադրամ)
This study aims to assess the dietary exposure of trans-fatty (TFA) acids through the consumption of ice-cream in Yerevan. To this end, 24-hour dietary recall method is used to investigate the ice-cream consumption. TFA contents in icecream samples are determined using gas chromatography-mass spectrometry. On the average, people consume 0.018 g/day TFA through ice-cream for the whole year, while 0.111 g/day in summer. TFA intake through ice-cream consumption accounts for 0.007 % and 0.041 % of the total energy intake for a year and for summer season, respectively. Comparing with the WHO’s threshold (less than 1 % of total energy), the daily intake of TFAs via ice-cream consumption during summer warrants some concerns.
Keywords: Food Science and Technology